Role of environmental pollutants-induced ferroptosis in pulmonary diseases - Yang, Long; Qiao, Yongkang; Huang, Zeyu; Chen, Yuzhu; Zhang, Enxi; Liu, Zhiwei; Wang, Yuxuan; Chen, Shaobo; Dong, Jinrui; Liu, Bin (Frontiers in Medicine, 2025)
Respiratory diseases rank among the foremost causes of mortality and disability globally, with long-term exposure to environmental pollutants playing a critical role in their onset and progression. Despite this, the underlying mechanisms and effective targeted treatments for these disorders remain poorly understood, highlighting an urgent need for focused research. Cell death, a programmed cellular response to external harmful stimuli, including ferroptosis—a recently identified form of iron-dependent programmed cell death—emerges as a pivotal process. Characterized by intracellular iron accumulation and lipid peroxidation, ferroptosis appears intricately linked to lung injury induced by environmental pollutants. This review examines the role of ferroptosis in lung diseases triggered by environmental factors, aiming to shed light on its specific pathophysiological mechanisms and potential as a therapeutic target. By deepening our understanding of the interactions between environmental pollution, ferroptosis, and lung damage, we hope to inform strategies for effective intervention.